2002
DOI: 10.1103/physreve.65.051603
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for an original two-dimensional phase structure: An antiparallel semifluorinated monolayer at the air-water interface

Abstract: We show the spontaneous formation of an antiparallel monolayer of diblock semifluorinated n-alkane molecules spread at the air-water interface. We used simultaneous measurements of surface pressure and surface potential versus molecular area and performed grazing x-ray reflectivity experiments to characterize the studied monolayer, which is obtained at almost zero surface pressure and precedes the formation of a bilayer at higher surface pressure. Its thickness, equal to 2.7 nm, was found to be independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The F 14 H 20 molecules have a dipole of 3.1 D oriented along the chain at the central –CF 2 –CH 2 -junction. Therefore, macroscopic Kelvin probe studies of Langmuir–Blodgett layers of different F n H m revealed a strong surface potential of −0.8 V [67] that is assigned to vertically oriented molecular chains with fluorinated parts facing air. Therefore, the fluoroalkane structures are the useful models for the verification of KFM operations.…”
Section: Resultsmentioning
confidence: 99%
“…The F 14 H 20 molecules have a dipole of 3.1 D oriented along the chain at the central –CF 2 –CH 2 -junction. Therefore, macroscopic Kelvin probe studies of Langmuir–Blodgett layers of different F n H m revealed a strong surface potential of −0.8 V [67] that is assigned to vertically oriented molecular chains with fluorinated parts facing air. Therefore, the fluoroalkane structures are the useful models for the verification of KFM operations.…”
Section: Resultsmentioning
confidence: 99%
“…This molecular orientation was also supported by surface potential measurements on Langmuir monolayers, revealing an egative surfacep otential. [12][13][14] However, an antiparallel conformation for FnHm diblocks [15] and the formation of as mecticb ilayer [16] have been proposed, too. Disk-like and striped surface domains were also reportedf or partially fluorinated carboxylic acids [17] and partially fluorinated diether glycerols, [18] respectively.S urfaced omains of variouss hapes were also published for combinations of fluorinated amphiphiles (phosphates, diethyl glycerols) with hydrocarbon and fluorocarbon oils [19] or phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Kelvin probe studies of Langmuir-Blodgett films of different F n H m~n ϭ 12, 14, m ϭ 8, 12, 20! revealed that the fluoroalkanes' self-assemblies exhibit strong surface potential of Ϫ0.8V~El Abed et al, 2002;Broniatowski et al, 2004!. These results, which are explained by vertical orientation of molecular dipole at the central -CF 2 -CH 2 -junction, serve as a valuable reference for KFM. The KFM and dC/dz data obtained on self-assemblies F 12 H 10 , F 12 H 20 , and F 14 H 20 on different substrates, which are partially described elsewherẽ Alexander et al, 2009;, 2011!…”
Section: Resultsmentioning
confidence: 84%
“…Kelvin probe studies of Langmuir-Blodgett films of different F n H m ( n = 12, 14, m = 8, 12, 20) revealed that the fluoroalkanes' self-assemblies exhibit strong surface potential of −0.8V (El Abed et al, 2002; Broniatowski et al, 2004). These results, which are explained by vertical orientation of molecular dipole at the central -CF 2 -CH 2 - junction, serve as a valuable reference for KFM.…”
Section: Resultsmentioning
confidence: 99%